2021
DOI: 10.3389/fphys.2021.773995
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Manipulation of Resistance Training Variables Promotes Myofibrillar Spacing Changes in Resistance-Trained Individuals

Abstract: We sought to determine if manipulating resistance training (RT) variables differentially altered the expression of select sarcoplasmic and myofibril proteins as well as myofibrillar spacing in myofibers. Resistance-trained men (n = 20; 26 ± 3 years old) trained for 8 weeks where a randomized leg performed either a standard (CON) or variable RT protocol (VAR: manipulation of load, volume, muscle action, and rest intervals at each RT session). A pre-training (PRE) vastus lateralis biopsy was obtained from a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…We hypothesized that there would be a decrease in myofibrillar area and an increase in non-myofibrillar area with type I and II fCSA increases following LL-BFR. In contrast, we hypothesized that HL-RT would promote conventional hypertrophy, consistent with findings from previous studies ( Fox et al, 2021 ; Ruple et al, 2021 ; Vann et al, 2022 ). Finally, we hypothesized that extracellular area would be greater following LL-BFR.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…We hypothesized that there would be a decrease in myofibrillar area and an increase in non-myofibrillar area with type I and II fCSA increases following LL-BFR. In contrast, we hypothesized that HL-RT would promote conventional hypertrophy, consistent with findings from previous studies ( Fox et al, 2021 ; Ruple et al, 2021 ; Vann et al, 2022 ). Finally, we hypothesized that extracellular area would be greater following LL-BFR.…”
Section: Introductionsupporting
confidence: 81%
“…Conventional hypertrophy, or the proportional increase in myofibrillar area with an increase in fCSA, has recently been challenged by studies that demonstrated sarcoplasmic expansion after some resistance training protocols. For example, Fox et al (2021) compared traditional HL-RT with a protocol with frequent manipulation of resistance training variables (e.g., load, sets, muscle action, and rest). In contrast to what was observed after HL-RT, the protocol with variation in exercise stimulus induced an increase in the non-myofibrillar area after 16 resistance training sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, serial sections were allowed to air dry for ∼1.5-2 h at room temperature followed by fixation in chilled acetone (−20 objective. According to previous reports, the quantification of myofibril area per fibre was performed using ImageJ software (Fox et al, 2021;Ruple et al, 2021). Briefly, the relative scale within ImageJ was set such that 1 pixel was equivalent to 0.451 μm, images were then split into RGB channels, and the red, phalloidin-containing channel was converted to greyscale.…”
Section: Ihc For Phalloidin-actin Stainingmentioning
confidence: 99%